Tingkat Kecemasan Dental Mahasiswa Fakultas Kedokteran di Masa Pandemi Covid-19 - Aqillah Aeriza Putti (Jurnal Medika Hutama, 2022)
Background: Covid-19, the new variant of coronavirus founded in 2019, spreads through droplets thus causing a worldwide pandemic and impacts on psychological conditions such as anxiety. On the other hand, dental procedures produce a lot of aerosols containing bacteria, fungi, and viruses from the patient’s mouth, resulting in increased anxiety about visiting the dentist in the presence of this virus. As a medical student with heavy learning load and is in their teenage years, an increasing in anxiety is common from both academic and aesthetic perspectives, so that dental health cannot be ruled out. Excessive anxiety about this virus can interfere with learnings and continuation of ongoing dental care. Therefore, assessing the patient’s anxiety level is essential as a dentist in order to continue treatments amidst the pandemic Objective: To find out the level of dental anxiety of medical students towards dental visits during the Covid-19 pandemic. Method: The type of research used is descriptive observational with a cross sectional design. The study was conducted by distributing questionnaires to 100 students of the Faculty of Medicine, Trisakti University class 2018, 2019, and 2020. Results: The level of anxiety towards dental visits are 1% no anxiety, 24% mild anxiety, 236% moderate anxiety, and 23% severe anxiety, and 16% extreme anxiety. Conclusion: Students of the Faculty of Medicine, Trisakti University class 2018, 2019, and 2020 experienced mild anxiety towards dental visits during the Covid-19 pandemic.